Economic Evaluations of Strategies to Prevent Hospital-Acquired Pressure Injuries. (July 2017) - Ocampo, Wrechelle; Cheung, Amanda; Baylis, Barry; Clayden, Nancy; Conly, John M.; Ghali, William A.; Ho, Chester H.; Kaufman, Jaime; Stelfox, Henry T.; Hogan, David B.
Abstract : GENERAL PURPOSE: To provide information from a review of literature about economic evaluations of preventive strategies for pressure injuries (PIs). TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant should be better able to: 1. Identify the purpose and methods used for this study. 2. Compare costs and effectiveness related to preventative strategies for PIs. ABSTRACT: BACKGROUND: Pressure injuries (PIs) are a common and resource-intensive challenge for acute care hospitals worldwide. While a number of preventive strategies have the potential to reduce the cost of hospital-acquired PIs, it is unclear what approach is the most effective. OBJECTIVE: The authors performed a narrative review of the literature on economic evaluations of preventive strategies to survey current findings and identify important factors in economic assessments. DATA SOURCES: Ovid, MEDLINE, NHS Economic Evaluation Databases, and the Cochrane Database of Systematic Reviews SELECTION CRITERIA: Potentially relevant original research articles and systematic reviews were considered. DATA EXTRACTION: Selection criteria included articles that were written in English, provided data on cost or economic evaluations of preventive strategies of PIs in acute care, and published between January 2004 and September 2015. Data were abstracted from the articles using a standardized approach to evaluate how the items on the Consolidated Health Economic Evaluation Reporting Standards checklist were addressed. DATA SYNTHESIS: The searches identified 192 references. Thirty-three original articles were chosen for full-text reviews. Nineteen of these articles provided clear descriptions of interventions, study methods, and outcomes considered. CONCLUSIONS: Limitations in the available literature prevent firm conclusions from being reached about the relative economic merits of the various approaches to the prevention of PIs. The authors' review revealed a need for additional high-quality studies that adhere to commonly used standards of both currently utilized and emerging ways to prevent hospital-acquired PIs.